Artificial intelligence and academic integrity in higher education: Evidence from student use of AI tools - Dedi Irwan; Ardila Venesa; Fatimah Azzahra Rabiah; Febiola Esfandiani Geraldine; Akwilia Setya Mirandea (Jurnal Pendidikan Informatika dan Sains, 2025)
The rapid integration of artificial intelligence (AI) into higher education has transformed how students approach academic learning and task completion, raising both pedagogical opportunities and ethical concerns. This study investigates patterns of AI use, perceived benefits, and integrity-related challenges among pre-service English teachers in a higher education context. Using a descriptive quantitative design, data were collected from 338 pre-service teachers through a structured online questionnaire and analysed using descriptive statistics. The findings reveal an exceptionally high level of AI adoption, with 98.2% of respondents reporting regular use of AI tools to support their academic activities, indicating that AI has become embedded in students’ everyday learning routines. However, AI use was found to be predominantly efficiency-oriented, with 44.1% of students using AI primarily for task completion and 40.8% for time efficiency, while only 15.1% reported using AI to explicitly enhance academic quality. Despite this instrumental orientation, students demonstrated substantial ethical awareness, as 72.8% acknowledged that AI has the potential to undermine academic integrity, particularly in relation to honesty and originality. At the same time, AI was perceived to offer meaningful learning-related benefits. A majority of respondents (68.6%) reported improvements in the quality of their academic outputs when using AI, describing their work as more structured, accurate, and polished. Furthermore, 77.5% of students indicated increased confidence in completing academic tasks with AI support, suggesting that AI may function as a form of cognitive and affective scaffolding. Overall, the study highlights the dual role of AI in higher education as both a productivity-enhancing learning support tool and a source of ethical tension. These findings underscore the need for clear institutional guidelines, ethical literacy, and pedagogical strategies that promote responsible, reflective, and learning-oriented use of AI in teacher education.